Reframing Structural Relationships and Institutional Performance in LocalGovernment: A Collaborative Approach to Poverty Alleviation in Malang City - Azizi, Dimas Irfan; Agustin, Chairina Fitri (PANGRIPTA, 2024)
This study examines the dynamics of local government in Malang City in addressing poverty through a collaborative governance approach. Malang remains a key contributor to East Java's poverty rate, making it a complex case for poverty alleviation. Using qualitative methods, the research evaluates institutional frameworks, structural relations, and advocacy coalitions in the government's poverty reduction strategies. Findings show that although poverty reduction is aligned with key documents like the RPJMD 2016–2021, there is no formal legal framework for collaboration. Cooperation between government bodies occurs mostly horizontally, with minimal involvement from NGOs and the private sector. Additionally, a lack of integrated coordination limits the effectiveness of collaborative governance. The limited participation of external actors weakens advocacy coalitions, reducing the impact of policies. This study contributes to the discourse on improving institutional performance and collaboration in poverty alleviation, emphasizing the need for a stronger multi-sectoral approach. The findings suggest practical recommendations for reinforcing collaborative frameworks to address poverty challenges more effectively.